The future of the nuclear non-proliferation treaty: Perspectives in advance of the 2005 review conference - Oliver Thränert (Stiftung Wissenschaft und Politik (SWP), 2004)
The proliferation of nuclear weapons is a great challenge facing international relations. Having established a norm for the non-proliferation of nuclear weapons that has been accepted by almost every country, the Treaty on the Non-Proliferation of Nuclear Weapons (simply: Non-Proliferation Treaty; NPT) which went into effect in 1970, has played a key role in keeping the world from being engulfed by nuclear weapons. In addition to non-proliferation, the NPT is based on the pledge by the five nuclear powers to disarm and an agreement to cooperate internationally in the use of nuclear energy for peaceful purposes. Nevertheless there existed a considerable degree of tension between the treaty's three pillars which has intensified markedly in recent years.The next NPT Review Conference will take place in May 2005 against this background. Which position should Germany take at the NPT Review Conference in order to strengthen the NPT?Within the framework of the problem as stated above, the following six fields which will for the most part determine the NPT's future, are being analyzed: * Universality: How should the NPT signatories deal with the non-member states Israel, India, and Pakistan? * Verification: How to improve the verification of the treaty? * Disarmament Pledge: What about the nuclear disarmament of the nuclear powers? * Technology Transfer: How is it to be managed in the future? Will non-nuclear powers continue be allowed access to the complete nuclear fuel cycle? * Withdrawal: How to impede members from withdrawing from the NPT (a step that is at present relatively simple)? * Treaty Compliance: What has to happen when a state violates the NPT? (SWP-Research Papers / SWP)
Keywords: 320